Business Planning - Jati , Agan Rista; Mulyani , Ana Susi; Cakradipura, Muhammad Rafli; Sitompul, Hotmar Daniel; Putri , Ayu Agustia; Fitriah , Ade (PT FORMOSA CENDEKIA GLOBAL, 2024)
The business planning discussed in this article includes the objectives of business planning, the stages of preparing a business plan, the importance of making a business plan, components, and things that need to be considered in business planning. Business planning is designed so that the business you own has thorough preparation, so that it is easier to achieve success than not having a prepared plan at all. In a business plan, the business concept, market, finances and so on are generally outlined in detail. Planning a business is very important for business people, so that the business continues to run stably and becomes more successful. Without a mature plan, entrepreneurs will not be able to achieve success.